PENGEMBANGAN BUKU ELEKTRONIK BERBASIS FLIP PDF PROFESSIONAL PADA MATERI SISTEM RESPIRASI KELAS XI SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This development aims to produce a Professional Flip PDF Based E-book on Quality Materials on the Class XI High School Respiration System. The research was carried out at the Biology Education Study Program, FKIP UNRI, a zoom meeting platform and at school for SMA Negeri 2 Pekanbaru students in November 2021 - January 2022. The subject of this research was KD 3.7 material on the respiratory system class XI SMA. The type of research used is Research and Development (R&D) ADDIE model. The instrument used is a validation sheet. The validation sheet consists of 4 aspects, namely display aspects, program aspects, content aspects and language aspects. The results of the validation of the professional flip pdf-based e-book on the respiratory system material for class XI SMA shows that the e-book that has been developed is in the very valid category with an overall average score of 3.82. The four aspects include the display aspect with an average of 3.82, the program aspect with an average of 3.83, the content aspect with an average of 3.83 and the language aspect with an average of 3.80. The aspect that received the highest score was the program aspect and the content aspect with the same average score of 3.83 being in the very valid category. The results of the first stage of the trial obtained an average score of 3.73 and the results of the second stage of the trial obtained an average score of 3.72 in the very good category. The results showed that the e-book developed was good and suitable to be used as a reference for learning in schools as well as a source of independent learning to increase students' knowledge and understanding of the respiratory system material in facilitating students to build their own knowledge.Key Words: Electronic Book, Flip PDF Professional, Respiratory System